Two-dimensional mesoporous nano material as well as preparation method and application thereof

Two-dimensional mesoporous nanomaterials were prepared by electrochemical synthesis, which solved the problem of low catalytic activity caused by the small pore size of two-dimensional MOF materials and enabled efficient catalytic reaction applications.

CN121064490APending Publication Date: 2025-12-05QINGDAO DIAISHENG INNOVATION TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511135938.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-14
Publication Date
2025-12-05

AI Technical Summary

Technical Problem

The pore size of two-dimensional MOF materials is less than 2 nm, which leads to insufficient contact between the reaction substrate and the active site, resulting in low catalytic activity.

Method used

Two-dimensional mesoporous nanomaterials were prepared by electrochemical synthesis. By applying a voltage between the anode and cathode, a multidentate coordinated metal-organic framework material was formed, constructing a highly crystalline and porous skeleton. The pore size distribution of the material was 2-50 nm, the thickness was 0.5-20 nm, and it had a high specific surface area.

Benefits of technology

We have achieved large-scale, low-cost, and rapid preparation of two-dimensional mesoporous nanomaterials with high active sites, which are suitable for electrocatalytic water splitting, electrocatalytic CO2 reduction, photocatalysis, or heterogeneous catalysts, thus improving catalytic reaction efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121064490A_ABST
    Figure CN121064490A_ABST
Patent Text Reader

Abstract

The invention discloses a two-dimensional mesoporous nano material and a preparation method and application thereof, the nano material comprises a metal-organic framework material, the metal-organic framework material comprises a ligand compound containing a plurality of carboxylate radical groups and metal ions, and the carboxylate radical groups are connected with the metal ions through coordinate bonds. According to the nano material in the embodiment of the invention, carboxylate radical groups and metal ions can form stable multidentate coordination, a framework material with high crystallinity and porosity is constructed, and the material is large in pore diameter, thin in thickness and relatively high in specific surface area, can provide richer active sites for catalytic reaction, and can be used for preparing a catalyst for catalytic reaction. The method can be applied to the fields of electro-catalysis water decomposition, electro-catalysis CO2 reduction, photocatalysts or heterogeneous catalysts and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of nanomaterials, and particularly relates to a two-dimensional mesoporous nanomaterial and a preparation method and application thereof. BACKGROUND

[0002] Metal-Organic Frameworks (MOF) is a new type of porous material, which has potential application value in the fields of gas adsorption / separation / storage, catalyst, fluorescent sensing, biological medicine, etc. due to its high porosity, large specific surface area and designable metal center and ligand. MOF can be divided into two-dimensional and three-dimensional MOFs according to the dimension. Compared with three-dimensional MOF, two-dimensional MOF has an ultra-thin thickness, a large lateral size and rich exposed active sites, and is more conducive to application in the field of catalysts. However, the pore size of two-dimensional MOF is usually less than 2 nm, which belongs to microporous material. The narrow microporous channel inside the material hinders the effective contact between the reaction substrate (especially the substrate with a large molecular size) and the active sites in the MOF framework to a certain extent. Due to the small number of accessible active sites, the catalytic activity is low. SUMMARY

[0003] The purpose of the embodiments of the application is to provide a two-dimensional mesoporous nanomaterial and a preparation method and application thereof, so as to solve the problem of low catalytic activity due to the small number of accessible active sites of the material.

[0004] In a first aspect, the embodiments of the application provide a two-dimensional mesoporous nanomaterial, comprising:

[0005] a metal-organic framework material, wherein the metal-organic framework material comprises a ligand compound containing a plurality of carboxylate groups and metal ions, and the carboxylate groups are connected to the metal ions by coordination bonds.

[0006] Optionally, the nanomaterial has a layered or sheet-like structure; and / or

[0007] the nanomaterial has a sheet-like structure, and the thickness of the nanomaterial is 0.5-20 nm; and / or

[0008] the pore size distribution of the nanomaterial is 2-50 nm; and / or

[0009] the pore volume of the nanomaterial is 0.01-3.0 cm3 / g.

[0010] Optionally, the ligand compound comprises:

[0011] 2,5-furandicarboxylic acid.

[0012] Optionally, the metal ions comprise:

[0013] at least one of nickel, iron, zinc, copper, manganese, tin, aluminum, bismuth, vanadium, molybdenum ions.

[0014] In a second aspect, the embodiment of the present application provides a preparation method of two-dimensional mesoporous nanomaterials, comprising:

[0015] Dissolving the ligand compound and the metal source in a solvent to obtain an electrolyte;

[0016] Pouring the electrolyte into an electrolytic cell, and applying a voltage between the anode and the cathode to perform electrochemical synthesis;

[0017] The electrochemical synthesis is performed for 0.1-24 hours;

[0018] Separating the nanocompounds generated on the electrodes and the nanocompounds generated in the electrolyte, and drying the nanocompounds to obtain the two-dimensional mesoporous nanomaterials.

[0019] Optionally, the reaction temperature of the electrochemical synthesis is 0-90℃; and / or

[0020] The molar ratio of the ligand compound and the metal source is 0.1-10; and / or

[0021] The voltage is 1-100V; and / or

[0022] The anode is selected from at least one of iron sheet, copper sheet, zinc sheet, and nickel sheet, and the cathode is selected from at least one of nickel foam, zinc sheet, copper foam, iron foam, carbon felt, graphite felt, iron sheet, copper sheet, and nickel sheet; and / or

[0023] Before the step of applying a voltage between the anode and the cathode to perform electrochemical synthesis, the method further comprises: cleaning the anode and the cathode; and / or

[0024] The step of drying the nanocompounds comprises: placing the nanocompounds in a vacuum dryer at 20-200℃ for 2-12 hours.

[0025] Optionally, the ligand compound comprises:

[0026] 2,5-furandicarboxylic acid; and / or

[0027] The metal ions comprise at least one of nickel, iron, zinc, copper, manganese, tin, aluminum, bismuth, vanadium, and molybdenum ions; and / or

[0028] The metal source is an acetate metal source; and / or

[0029] The solvent is selected from at least one of dimethylformamide, dimethylacetamide, glacial acetic acid, methanol, ethanol, and water.

[0030] Optionally, the electrolyte further comprises:

[0031] A surfactant.

[0032] Optionally, the surfactant comprises:

[0033] at least one of hexadecyl trimethyl ammonium bromide, octadecyl trimethyl ammonium bromide, dodecyl trimethyl ammonium bromide, tetrabutyl ammonium bromide and tetrabutyl ammonium tetrafluoroborate; and / or

[0034] The molar ratio of the metal source to the surfactant is (1:0.01)-(1:5).

[0035] In a third aspect, the embodiments of the present application provide the application of the nanomaterials described in the above embodiments or the nanomaterials prepared by the preparation method described above in the fields of electrocatalytic water splitting, electrocatalytic CO2 reduction, photocatalysts or heterogeneous catalysts.

[0036] The two-dimensional mesoporous nanomaterials of the embodiments of the present application comprise:

[0037] The metal-organic framework material comprises a ligand compound containing a plurality of carboxylate groups and metal ions, and the carboxylate groups are connected to the metal ions by coordination bonds. In the nanomaterials of the embodiments of the present application, the plurality of carboxylate groups can form stable polydentate coordination with the metal ions, constructing a high-crystallinity and porous framework material. The material has a large pore size, a thin thickness, a high specific surface area, and can provide more active sites for catalytic reactions, and can be suitable for the fields of electrocatalytic water splitting, electrocatalytic CO2 reduction, photocatalysts or heterogeneous catalysts, etc. BRIEF DESCRIPTION OF DRAWINGS

[0038] Figure 1 The FTIR spectrum of the NiFe-FDCA MOF mesoporous material prepared in Example 1;

[0039] Figure 2 The SEM image of the NiFe-FDCA MOF mesoporous material prepared in Example 1;

[0040] Figure 3 The TEM image of the NiFe-FDCA MOF mesoporous material prepared in Example 1;

[0041] Figure 4 The TEM image of the NiFe-FDCA MOF mesoporous material prepared in Example 1 after water treatment for 24 hours;

[0042] Figure 5 The nitrogen adsorption and desorption isotherm of the Cu-FDCA MOF prepared in Example 4;

[0043] Figure 6 The nitrogen adsorption and desorption isotherm of the Cu-BTC MOF prepared in Comparative Example 3;

[0044] Figure 7 OER performance plots for the NiFe-FDCA MOF, Fe-FDCA MOF, and AlNiFe-FDCA MOF prepared for Example 1, Example 2, and Example 8. DETAILED DESCRIPTION

[0045] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the drawings in the embodiments of the present application. Obviously, the described embodiments are some of the embodiments of the present application, rather than all the embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by a person of ordinary skill in the art without creative work are within the protection scope of the present application.

[0046] The terms "first", "second", and the like in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than those illustrated or described herein. In addition, "and / or" in the specification and claims indicates at least one of the connected objects, and the character " / ", generally indicates that the front and rear associated objects are in a "or" relationship.

[0047] The two-dimensional mesoporous nanomaterials of the embodiments of the present application include:

[0048] The metal-organic framework material includes a ligand compound containing a plurality of carboxylate groups and metal ions, and the carboxylate groups are connected to the metal ions by coordination bonds. In the nanomaterials of the embodiments of the present application, the plurality of carboxylate groups can form stable polydentate coordination with the metal ions, constructing a high-crystallinity and porous framework material. The material has a large pore size and a thin thickness, has a high specific surface area, can provide more active sites for catalytic reactions, and can be applied to the fields of electrocatalytic water splitting, electrocatalytic CO2 reduction, photocatalysts, or heterogeneous catalysts, etc. In addition, the material can be prepared by an electrochemical synthesis method, which can realize large-scale synthesis of metal-organic frameworks in the form of powder or thin film with milder reaction conditions and faster reaction speed.

[0049] In some embodiments, the nanomaterials can have a layered or sheet-like structure.

[0050] Optionally, the nanomaterials are in a sheet-like structure, and the thickness of the nanomaterials can be 0.5-20 nm, preferably 3-5 nm.

[0051] Optionally, the nanoporous material has a pore size distribution of 2-50 nm, preferably the nanoporous material has a pore size distribution of 14-22 nm.

[0052] In some embodiments, the nanoporous material has a pore volume of 0.01-3.0 cm3 / g, preferably the nanoporous material has a pore volume of 0.01-0.75 cm 3 / g.

[0053] In some embodiments, the ligand compound can include:

[0054] 2,5-furandicarboxylic acid.

[0055] In some embodiments, the metal ion can include:

[0056] at least one of nickel, iron, zinc, copper, manganese, tin, aluminum, bismuth, vanadium, and molybdenum. For example, the compound can be selected as 2,5-furandicarboxylic acid, the metal ion can be selected as one of nickel, iron, and zinc, or the metal ion can be selected as nickel and iron.

[0057] The solvent can be selected from at least one of dimethylformamide (DMF), dimethylacetamide, glacial acetic acid, methanol, ethanol, and water. Preferably, a mixed solvent (such as a DMF / water system) can be used as the electrolyte, which significantly improves the solubility of the ligand.

[0058] A method for preparing a two-dimensional mesoporous nanoporous material according to an embodiment of the present application includes:

[0059] dissolving a ligand compound and a metal source in a solvent to obtain an electrolyte;

[0060] pouring the electrolyte into an electrolytic cell, and applying a voltage between an anode and a cathode to perform electrochemical synthesis;

[0061] the electrochemical synthesis is performed for 0.1-24 hours;

[0062] separating the nanoporous compound generated on the electrode and the nanoporous compound generated in the electrolyte, drying the nanoporous compound, and obtaining the two-dimensional mesoporous nanoporous material.

[0063] The nanomaterial prepared by the method in the embodiment of the application can form stable multidentate coordination with metal ions through the ligand compound containing multiple carboxylate groups, can construct a high-crystallinity and high-porosity skeleton material, has a large pore size and a thin thickness, has a high specific surface area, can provide more active sites for catalytic reactions, and can be applied to the fields of electrocatalytic water splitting, electrocatalytic CO2 reduction, photocatalysts or heterogeneous catalysts, etc. The metal-organic framework in powder or film form can be synthesized on a large scale through the electrochemical synthesis method, which can realize large-scale synthesis under milder reaction conditions and at a faster reaction speed. The electrode in-situ growth strategy can realize efficient preparation of the MOF material, and the time-space yield can be as high as 393 kg / m 3 / day, the metal-ligand coordination rate is improved by 2-3 orders of magnitude, and the problems of long time consumption and low yield in the preparation of MOF through the traditional hydrothermal method are solved. Meanwhile, the two-dimensional mesoporous MOF nanomaterial obtained in the application has a low OER overpotential, the regular two-dimensional structure and the rich mesoporous system provide high active sites and fast mass transfer channels for catalytic reactions, and the nanomaterial has a wide application prospect when applied to the field of electrocatalysis, etc.

[0064] In the embodiment of the application, the reaction temperature of the electrochemical synthesis can be 0-90 DEG C, and preferably, the reaction temperature of the electrochemical synthesis can be 20-50 DEG C.

[0065] The molar ratio of the ligand compound and the metal source can be 0.1-10.

[0066] The voltage can be 1-100 V, and preferably, the voltage can be 5-15 V. A direct current voltage can be selected, the direct current voltage drives the directional migration of metal ions and furan dicarboxylic acid to the surface of the electrode through an electric field, realizes accurate control of the local concentration, promotes uniform nucleation and ordered growth, forms a strong coordination bond between the metal nodes and the furan dicarboxylic acid, and enhances the electron transport capacity of the MOF skeleton. The direct current electrochemical method supports continuous production and is more conducive to industrial application.

[0067] The anode can be at least one selected from iron sheets, copper sheets, zinc sheets and nickel sheets, and the cathode can be at least one selected from nickel foam, zinc sheets, copper foam, iron foam, carbon felt, graphite felt, iron sheets, copper sheets and nickel sheets.

[0068] Before the step of applying a voltage between the anode and the cathode to perform electrochemical synthesis, the method can further include: cleaning the anode and the cathode.

[0069] During the pretreatment of the electrode, the solvent ultrasonic cleaning, acid pickling and water washing and drying can be sequentially performed.

[0070] The step of drying the nanocompound can include: placing the nanocompound in a vacuum drying oven at 20-200 DEG C for 2-12 h.

[0071] In some embodiments, the ligand compound can comprise:

[0072] 2,5-furan dicarboxylic acid.

[0073] Optionally, the metal ion can comprise at least one of nickel, iron, zinc, copper, manganese, tin, aluminum, bismuth, vanadium, molybdenum ion; and / or

[0074] The metal source is an acetate metal source; and / or

[0075] The solvent is selected from at least one of dimethylformamide, dimethylacetamide, glacial acetic acid, methanol, ethanol and water.

[0076] The compound can be selected as 2,5-furan dicarboxylic acid, and the metal source can be selected as metal acetate. The metal acetate not only provides metal ions, but also, during the process of electricity, acetate ions are reduced at the cathode (CH3COO - + 2H + + 2e-→ CH3CH2OH + H2O), consuming H + in the system, achieving in-situ deprotonation of furandicarboxylic acid. In the mixed solvent containing water, acetate ions also undergo hydrolysis to produce acetic acid and OH - (CH3COO - + H2O = CH3COOH + OH - ), providing the necessary OH - for the deprotonation of furan dicarboxylic acid without the need for additional addition of alkali (such as sodium hydroxide) to achieve deprotonation. The "double deprotonation" greatly improves the rate of deprotonation of furandicarboxylic acid. The deprotonated FDC 2- immediately coordinates with metal cations at the cathode, and in-situ MOF deposition is carried out, improving the generation rate of FDCA-MOF. In addition, the acetic acid produced by the hydrolysis of acetate can play a role in adjusting the size of MOF, without the need for additional addition of monobasic acid as a size-adjusting additive. Compared with the commonly used nitrate in electrochemical method, the radius of acetate ion is smaller, and it is easier to remove during washing, and it is not easy to remain in the pores of MOF, ensuring that the obtained MOF material has a larger pore size and pore volume.

[0077] In some embodiments, the electrolyte can further comprise:

[0078] A surfactant. The surfactant can be selected as a quaternary ammonium salt surfactant. The adsorption of quaternary ammonium salt can modify the electrode surface, reduce the nucleation barrier of metal ions and furan dicarboxylic acid ligand, promote uniform deposition, and quaternary ammonium salt surfactant can avoid local concentration unevenness caused by insufficient solubility of ligand, thereby improving the crystallinity of MOF.

[0079] Optionally, the surfactant can include:

[0080] at least one of hexadecyl trimethyl ammonium bromide, octadecyl trimethyl ammonium bromide, dodecyl trimethyl ammonium bromide, tetrabutyl ammonium bromide and tetrabutyl ammonium tetrafluoroborate.

[0081] By the combination of the acetic acid salt metal source, the quaternary ammonium salt supporting electrolyte and the aqueous mixed solvent, the 2,5-furan dicarboxylic acid ligand and different transition metal ions can form the two-dimensional sheet-shaped MOF mesoporous material after being electrified, the ultra-thin two-dimensional sheet-shaped MOF structure formed can expose more active sites, can reduce the mass transfer resistance and better transport electrons.

[0082] The molar ratio of the metal source to the surfactant can be (1:0.01)-(1:5), for example, the molar ratio of the metal source to the surfactant can be 1:0.9.

[0083] In the application, the NiFe-FDCA MOF is prepared by the electrochemical synthesis method, can be synthesized in a short time of 0.1-2h under mild conditions of 20-50℃, has high space-time yield, is green, environmentally friendly and low in energy consumption cost, and can realize large-scale production of the MOF in the form of powder or film; the prior art is to synthesize the NiFe-FDCA MOF by using the traditional hydrothermal method, the reaction device of the method is an autoclave, needs to react at high temperature of 180-220℃ for a long time of 12-24h, is poor in safety, high in energy consumption cost, is affected by low solubility of raw materials, can only react at a very low concentration, is low in space-time yield and difficult to realize large-scale industrial production.

[0084] In the reaction system of the electrochemical synthesis of the NiFe-FDCA-MOF, no additional alkali is needed to provide OH - , but in the electrification process, the acetate ions are reduced at the cathode (CH3COO - +2H + +2e-→CH3CH2OH+H2O), consume H + in the system, realize in-situ deprotonation of the furandicarboxylic acid; in the presence of water, the acetate ions in the system also hydrolyze (CH3COO - +H2O→CH3COOH+OH - ), generate OH - ions needed for in-situ deprotonation of the furandicarboxylic acid; the "double deprotonation" greatly improves the deprotonation rate of the furandicarboxylic acid; after deprotonation, the FDC 2-The immediate coordination with metal cations at the cathode improves the generation rate of FDCA-MOF, and avoids the formation of metal hydroxide to affect the purity of MOFs or block the pores of MOFs, so that the mesoporous NiFe-FDCA MOF with high purity and high yield is obtained, and the average pore size is 14.2 nm. In the reaction system of the hydrothermal method for synthesizing FDCA-MOF in the prior art, sodium hydroxide needs to be added to provide OH - The deprotonation of furandicarboxylic acid can improve the solubility of FDCA in the water system, and the introduction of excess alkali will inevitably cause the metal ions to react with OH - The generation of metal hydroxide precipitate hinders the combination of metal ions and furandicarboxylic acid to form MOF or blocks the pores of MOF, and affects the yield, purity and pore size of the MOF material. In the reaction system for electrochemically synthesizing NiFe-FDCA-MOF in the present application, the molar ratio of 2,5-furandicarboxylic acid ligand to metal source can be close to 1:1, while in the prior art, the molar ratio of 2,5-furandicarboxylic acid ligand to the sum of ferrous source and nickel source is not less than 4:1. When the organic ligand is fed at 5 times the amount of metal salt, NiFe-FDC / NF is successfully constructed, which requires a considerable excess of FDCA, increasing the cost.

[0085] The application provides the application of the nanomaterial in the above-mentioned embodiments or the nanomaterial prepared by the preparation method in the application in electrocatalytic water splitting, electrocatalytic CO2 reduction, photocatalysts or heterogeneous catalysts.

[0086] The application will be further described below through some specific embodiments.

[0087] Embodiment 1

[0088] Preparation of NiFe-FDCA MOF

[0089] (1) Electrode pretreatment: 20 mm x 38 mm iron sheet (anode) and 20 mm x 38 mm nickel foam (cathode) are ultrasonically cleaned with ethanol for 15 min to remove surface oil stains, then washed with deionized water, and dried at room temperature, then soaked in 10% dilute hydrochloric acid to remove metal oxide film, and finally washed with deionized water and dried for standby;

[0090] (2) 0.9365 g of 2,5-furandicarboxylic acid, 0.7465 g of nickel acetate tetrahydrate, 0.5964 g of FeCl2·4H2O and 1.968 g of cetyltrimethylammonium bromide (CTAB) are dissolved in 60 ml of a mixed solvent of DMF and H2O (v / v = 1 / 1) as an electrolyte, wherein the molar ratio of 2,5-furandicarboxylic acid to metal source and CTAB is 10:10:9;

[0091] (3) Pour the electrolyte into a 100ml electrolytic cell. Fix the anode and cathode in the electrolytic cell with electrode clamps, ensuring that the electrolyte completely submerges the electrodes. The distance between the anode and cathode is 2cm. Use a DC regulated power supply HB1700-30V / 5A to provide current / voltage. Set the voltage to 10V and perform electrochemical synthesis at room temperature for 2 hours.

[0092] (4) Washing and Drying: The NiFe-FDCA MOF-loaded nickel foam electrode was washed three times each with DMF and ethanol, and then vacuum-dried at 80℃ for 8 hours to obtain the NiFe-FDCA MOF-loaded nickel foam electrode. After electrosynthesis, the electrolyte was centrifuged at 10,000 rpm, and the resulting reddish-brown precipitate was washed three times each with DMF and ethanol, and then vacuum-dried at 80℃ for 8 hours. A total of 2.1106 g of reddish-brown NiFe-FDCA MOF powder was obtained, with a space-time yield of 253.27 kg / m³. 3 / day.

[0093] Evaluation results of the material prepared in Example 1:

[0094] like Figure 1 As shown, the formation of FDCA-MOF can be confirmed based on FTIR results, with the FDCA molecule located at 1699.94 cm⁻¹. - The C=O peak at position 1 redshifted to approximately 1650 cm⁻¹ after the formation of the FDCA-MOF structure. - 1. Located at 1420.32cm - The CO bond of 1 redshifts to ~1360 cm⁻¹ after MOF formation. - 1. Furthermore, the intensity of both peaks is weakened to some extent, which is attributed to the coordination effect of the carboxyl group on the metal. For example... Figure 2 As shown in the SEM image, NiFe-FDCA-MOF is loaded onto nickel foam in a petal-like structure of 2D nanosheet stacks. Figure 3 As shown in the TEM image, the obtained NiFe-FDCA-MOF is an ultrathin two-dimensional nanosheet with a thickness of 3–5 nm and a uniform size of 200 nm. The average pore size of the MOF, measured using a Huapu Hengchuang fully automated pore size analyzer, is 14.214 nm. The pore volume is 0.752 cm³. 3 / g, BJH pore size distribution results show that the pores with a diameter of 30nm account for the largest proportion in MOF. The glassy carbon electrode supported on NiFe-FDCA-MOF (NiFe-FDCA-MOF / / GC) performs well under alkaline conditions at 10mAcm. -2 At current densities, the OER overpotential is as low as 405mV. For example... Figure 4 As shown in the TEM image, the NiFe-FDCA MOF still maintains an ultrathin two-dimensional sheet structure after 24 hours of water treatment, exhibiting excellent water stability.

[0095] Example 2

[0096] Preparation of Fe-FDCA MOF

[0097] (1) Electrode pretreatment: 20 mm x 38 mm Fe sheet was cleaned with ethanol for 15 min by ultrasonic to remove surface oil stains, then washed with deionized water, and dried at room temperature. Then it was immersed in 10% dilute hydrochloric acid to remove metal oxide film, and finally washed with deionized water and dried for standby use;

[0098] (2) 0.9365 g of 2,5-furan dicarboxylic acid and 2.0954 g of tetrabutylammonium bromide were dissolved in 60 ml of mixed solvent of DMF and glacial acetic acid (v / v = 5 / 1) as electrolyte. The molar ratio of 2,5-furan dicarboxylic acid to surfactant was 6:6.5;

[0099] (3) The electrolyte was poured into a 100 ml electrolytic cell, and the anode and cathode were fixed in the electrolytic cell with electrode clamps, so that the electrolyte completely immersed the electrodes. The distance between the anode and the cathode was 2 cm. A direct current stabilized power supply HB1700-30V / 5A was used to provide current / voltage, and the voltage was set to 10V. The electrochemical synthesis was carried out at room temperature, and the electro-synthesis time was 2h;

[0100] (4) Washing and drying: After the electrolyte after the end of the electro-synthesis was centrifuged at 10000 rpm, the MOF precipitate obtained was washed and centrifuged with DMF and ethanol for 3 times, and dried at 80℃ under vacuum for 8h. A total of 1.0693 g of Fe-FDCA MOF powder was obtained, and the space-time yield was 128.32 kg / m 3 / day.

[0101] Evaluation results of the material prepared in Example 2:

[0102] TEM image showed that the obtained Fe-FDCA-MOF was a two-dimensional nanosheet. The average pore size of the MOF tested by Huapu Hengchuang full-automatic pore size analyzer was 21.642 nm, and the pore volume was 0.1724 cm 3 / g. BJH pore size distribution results showed that the MOF had the most 30 nm pore size. The electro-catalytic water splitting OER test was the same as Example 1. The OER overpotential of the Fe-FDCA-MOF loaded glassy carbon electrode (Fe-FDCA-MOF / / GC) was 556 mV under alkaline conditions at a current density of 10 mA cm -2 .

[0103] Example 3

[0104] Preparation of Zn-FDCA MOF

[0105] (1) Electrode pretreatment: 20 mm x 38 mm zinc sheet was cleaned with ethanol ultrasonic for 15 min to remove surface oil, then washed with deionized water, air dried at room temperature, then soaked in 10% dilute hydrochloric acid to remove metal oxide film, and finally washed with deionized water and air dried for standby;

[0106] (2) 1.0926 g of 2,5-furan dicarboxylic acid and 1.1524 g of tetrabutylammonium tetrafluoroborate were dissolved in 50 ml of methanol as electrolyte. The molar ratio of 2,5-furan dicarboxylic acid to surfactant is 2:1;

[0107] (3) Pour the electrolyte into a 100 ml electrolysis cell, fix the anode and cathode with electrode clamps in the electrolysis cell, make the electrolyte completely immerse the electrodes, the distance between the anode and cathode is 2 cm, use a direct current stabilized power supply HB1700-30V / 5A to provide current / voltage, set the voltage to 10V, carry out electrochemical synthesis at room temperature, the electrochemical synthesis time is 2h;

[0108] (4) Washing and drying: After the electrolyte after the end of the electrochemical synthesis was centrifuged at 10000 rpm, the white precipitate obtained was washed with methanol and chloroform for 3 times, and centrifuged at 80℃ for 8h. The Zn-FDCA MOF powder obtained is 1.1528g, and the space-time yield is 105.51kg / m 3 / day;

[0109] Evaluation results of the material prepared in Example 3:

[0110] The average pore size of the MOF tested by Huapu Hengchuang full-automatic pore size analyzer is 14.35 nm, and the pore volume is 0.0131cm 3 / g.

[0111] Example 4

[0112] Electrochemical synthesis of Cu-FDCA MOF

[0113] (1) Electrode pretreatment: 20 mm x 38 mm zinc sheet was cleaned with ethanol ultrasonic for 15 min to remove surface oil, then washed with deionized water, air dried at room temperature, then soaked in 10% dilute hydrochloric acid to remove metal oxide film, and finally washed with deionized water and air dried for standby;

[0114] (2) 1.0926 g of 2,5-furan dicarboxylic acid and 1.1524 g of tetrabutylammonium tetrafluoroborate were dissolved in 50 ml of methanol as electrolyte. The molar ratio of 2,5-furan dicarboxylic acid to surfactant is 2:1;

[0115] (3) Pour the electrolyte into a 100 ml electrolytic cell, fix the anode and cathode with electrode clamps in the electrolytic cell, so that the electrolyte completely immerses the electrodes, wherein the distance between the anode and the cathode is 2 cm, use a direct current stabilized power supply HB1700-30V / 5A to provide current / voltage, set the voltage to 10V, and perform electrochemical synthesis at room temperature, and the electrochemical synthesis time is 2h;

[0116] (4) Washing and drying: after the electrochemical synthesis is completed, the electrolyte is centrifuged at 10000 rpm, and the blue precipitate obtained is washed and centrifuged with methanol and chloroform for 3 times, and vacuum dried at 60°C for 8h. The space-time yield of the Cu-FDCA MOF obtained is 138.34kg / m 3 / day. The average pore size of the MOF tested by the Huapu Hengchuang full-automatic pore size analyzer is 2.94nm. The pore volume is 0.1470cm 3 / g.

[0117] Evaluation results of the material prepared in Example 4:

[0118] The average pore size of the MOF tested by the Huapu Hengchuang full-automatic pore size analyzer is 2.94nm, and the pore volume is 0.147cm 3 / g.

[0119] Example 5

[0120] The difference between Example 5 and Example 1 is that:

[0121] The voltage is set to 1V, and the electrochemical synthesis is performed at 90°C, and the electrochemical synthesis time is 24h;

[0122] A total of 30.313g of red-brown NiFe-FDCA MOF powder is obtained, and the space-time yield is 303.13kg / m 3 / day.

[0123] Evaluation results of the material prepared in Example 5:

[0124] The average pore size of the MOF tested by the Huapu Hengchuang full-automatic pore size analyzer is 3.408nm, and the pore volume is 0.992cm 3 / g.

[0125] Example 6

[0126] The difference between Example 6 and Example 1 is that:

[0127] The voltage is set to 100V, and the electrochemical synthesis is performed at 0°C, and the electrochemical synthesis time is 10h;

[0128] A total of 6.1121g of NiFe-FDCAMOF powder is obtained, and the space-time yield is 146.69kg / m 3 / day.

[0129] Evaluation results of the material prepared in Example 6:

[0130] The average pore diameter of the MOF tested by the Huapu Hengcheng full-automatic pore size analyzer was 4.34 nm, and the pore volume was 0.299 cm 3 / g.

[0131] Example 7

[0132] The difference between Example 7 and Example 1 is that:

[0133] The voltage was set to 50 V, and the electrochemical synthesis was carried out at 50°C, and the electro-synthesis time was 1 h;

[0134] The NiFe-FDCA MOF powder obtained was 1.0873 g, and the space-time yield was 260.96 kg / m 3 / day.

[0135] Evaluation results of the material prepared in Example 7:

[0136] The average pore diameter of the MOF tested by the Huapu Hengcheng full-automatic pore size analyzer was 10.135 nm, and the pore volume was 0.0481 cm 3 / g.

[0137] Example 8

[0138] The difference between Example 8 and Example 1 is that:

[0139] (1) Electrode pretreatment: The 20 mm x 38 mm aluminum sheet (anode) and the 20 mm x 38 mm foam iron (cathode) were ultrasonically cleaned with ethanol for 15 min to remove surface oil stains, then washed with deionized water, and after air drying at room temperature, immersed in 10% dilute hydrochloric acid to remove metal oxide film, and finally washed with deionized water and air dried for standby use; The AlNiFe-FDCA MOF powder obtained was 2.2618 g, and the space-time yield was 271.52 kg / m 3 / day.

[0140] Evaluation results of the material prepared in Example 8:

[0141] The average pore diameter of the MOF tested by the Huapu Hengcheng full-automatic pore size analyzer was 6.766 nm, and the pore volume was 0.535 cm 3 / g.

[0142] Example 9

[0143] The difference between Example 9 and Example 1 is that:

[0144] (1) Electrode pretreatment: titanium sheet (anode) and cobalt sheet (cathode) with a size of 20 mm x 38 mm were ultrasonically cleaned with ethanol for 15 min to remove surface oil stains, then rinsed with deionized water, air-dried at room temperature, immersed in 10% dilute hydrochloric acid to remove metal oxide film, and finally rinsed with deionized water and air-dried for standby use; 2.3533 g of NiFe-FDCAMOF powder was obtained, with a space-time yield of 282.4 kg / m3 / day.

[0145] Evaluation results of the material prepared in Example 9:

[0146] The average pore size of the MOF tested by the Huapu Hengchuang full-automatic pore size analyzer was 24.661 nm, and the pore volume was 1.011 cm 3 / g.

[0147] Example 10

[0148] The difference between Example 10 and Example 1 is that:

[0149] (2) 0.0937 g of 2,5-furan dicarboxylic acid, 1.4930 g of nickel acetate tetrahydrate, 1.1929 g of FeCl2·4H2O and 0.1968 g of cetyltrimethylammonium bromide (CTAB) were dissolved in 60 ml of a mixed solvent of DMF and H2O (v / v = 1 / 1) as an electrolyte, wherein the molar ratio of 2,5-furan dicarboxylic acid to metal source, CTAB was 0.1:1:0.09; 0.8779 g of NiFe-FDCAMOF powder was obtained, with a space-time yield of 105.35 kg / m 3 / day.

[0150] Evaluation results of the material prepared in Example 10:

[0151] The average pore size of the MOF tested by the Huapu Hengchuang full-automatic pore size analyzer was 6.894 nm, and the pore volume was 0.156 cm 3 / g.

[0152] Example 11

[0153] The difference between Example 11 and Example 1 is that:

[0154] (2) 0.9365 g of 2,5-furan dicarboxylic acid, 0.1493 g of nickel acetate tetrahydrate, 0.1193 g of FeCl2·4H2O and 1.968 g of cetyltrimethylammonium bromide (CTAB) were dissolved in 60 ml of a mixed solvent of DMF and H2O (v / v = 1 / 1) as an electrolyte, wherein the molar ratio of 2,5-furan dicarboxylic acid to metal source, CTAB was 1:0.1:0.9; 3.2752 g of NiFe-FDCAMOF powder was obtained, and the space-time yield was 393.02 kg / m 3 / day.

[0155] Evaluation results of the material prepared in Example 11:

[0156] The average pore diameter of the MOF tested by the Huapu Hengchuang full-automatic pore size analyzer was 6.857 nm, and the pore volume was 0.588 cm 3 / g.

[0157] Example 12

[0158] The difference between Example 12 and Example 1 is that:

[0159] (2) 0.9365 g of 2,5-furan dicarboxylic acid, 0.1493 g of nickel acetate tetrahydrate, 0.1193 g of FeCl2·4H2O and 1.968 g of cetyltrimethylammonium bromide (CTAB) were dissolved in 60 ml of a mixed solvent of DMF and H2O (v / v = 1 / 1) as an electrolyte, wherein the molar ratio of 2,5-furan dicarboxylic acid to metal source, CTAB was 1:0.1:0.9; 3.2752 g of NiFe-FDCAMOF powder was obtained, and the space-time yield was 393.02 kg / m 3 / day.

[0160] Evaluation results of the material prepared in Example 12:

[0161] The average pore diameter of the MOF tested by the Huapu Hengchuang full-automatic pore size analyzer was 10.737 nm, and the pore volume was 0.174 cm 3 / g.

[0162] Comparative Example 1

[0163] Preparation of Zn-FDCA MOF by solvothermal method

[0164] Into a 25 mL Teflon-lined stainless steel autoclave, 2,5-furandicarboxylic acid (0.0468 g, 0.3 mmol), Zn(N03)2*6H20 (0.0892 g, 0.3 mmol), DMA (6 mL) and DMF (6 mL) were added, heated (100 °C, 48 h), cooled to room temperature at a rate of 2 °C / h, the crystals obtained from the reaction were separated from the solvent, dried at 65 °C under vacuum for 4 h, obtaining 0.0287 g of MOF powder, with a space-time yield of 0.574 kg / m 3 / day.

[0165] Comparative Example 2

[0166] Electrochemical synthesis of Zn-BDC MOF (MOF-5)

[0167] (1) Electrode pretreatment: a 20 mm x 38 mm zinc sheet was cleaned with ethanol by ultrasonic for 15 min to remove surface oil, then washed with deionized water, and dried at room temperature, then soaked in 10% dilute hydrochloric acid to remove the metal oxide film, and finally washed with deionized water and dried for standby use;

[0168] (2) 0.4984 g of terephthalic acid, 1.19 g of zinc nitrate hexahydrate and 5 g of 1-butyl-3-methylimidazolium bromide were dissolved in 40 ml of DMF as electrolyte, wherein the molar ratio of terephthalic acid to zinc nitrate hexahydrate was 3:4;

[0169] (3) The electrolyte was poured into a 100 ml electrolytic cell, the anode and cathode were fixed in the electrolytic cell with electrode clamps, the electrolyte was completely immersed in the electrodes, the distance between the anode and cathode was 2 cm, a direct current stabilized power supply HB1700-30V / 5A was used to provide current / voltage, the current was set to 0.2 A, and the electrochemical synthesis was carried out at room temperature, the electrochemical synthesis time was 2 h;

[0170] (4) Washing and drying: after the electrolyte after the electrochemical synthesis was centrifuged at 10000 rpm, the white precipitate obtained was washed with DMF and chloroform for 3 times respectively, and centrifuged, dried at 60 °C under vacuum for 8 h, obtaining 0.4363 g of Zn-BDC MOF powder, with a space-time yield of 52.36 kg / m 3 / day.

[0171] The average pore size of the MOF tested by the Huapu Hengchuang full-automatic pore size analyzer was 2.81 nm, and the porosity was 0.2921 cm 3 / g.

[0172] Comparative Example 3

[0173] Solvent-thermal synthesis of Cu-BTC MOF (HKUST-1)

[0174] Trimesic acid (0.2102 g, 2 mmol), Cu(NO3)2·3H2O (0.3624 g, 3 mmol), deionized water (5 mL) and ethanol (5 mL) were added into a 25 mL Teflon-lined stainless steel autoclave, heated (110 °C, 24 h), cooled to room temperature at a rate of 2 °C / h, and the crystals obtained from the reaction were separated from the solvent and dried at 65 °C under vacuum for 4 h. MOF powder 0.3913 g was obtained, with a space-time yield of 15.652 kg / m 3 / day.

[0175] The average pore size of the MOF tested by the Huapu Hengchuang full-automatic pore size analyzer was 1.52 nm, and the porosity was 0.5228 cm 3 / g.

[0176] Electrocatalytic water splitting OER test

[0177] The MOF sample materials prepared in the above Examples 1-4 were respectively subjected to electrocatalytic water splitting OER test.

[0178] (1) Preparation of catalyst ink:

[0179] 4 mg of the MOF sample prepared in the above Examples 1-4 and 2 mg of Ketjen black (MOF / Ketjen black = 2 / 1, w / w) were added into 1000 uL of anhydrous ethanol and 40 uL of a 5 wt% Nafion solution, and ultrasonic treatment was performed for 30 min to obtain catalyst ink. 10 uL of the catalyst ink was dropped on a glassy carbon electrode (diameter 5 mm), and after drying at room temperature, vacuum drying was performed at 65 °C for 3 h.

[0180] (2) Test of electrocatalytic OER performance of FDCA-MOF loaded glassy carbon electrode:

[0181] The equipment for OER test was CHI 760E electrochemical workstation. The three-electrode system was used for OER test under alkaline conditions, and the reaction conditions were as follows: 30 °C water bath heating, 1.0 M KOH solution, FDCA-MOF loaded glassy carbon electrode as working electrode, platinum sheet as counter electrode, Ag / AgCl as reference electrode, and the system was always purged with nitrogen; CV fast scan 20 times for catalyst activation, scan rate 0.1 V / s. LSV scan rate 5 mV / s; no iR correction.

[0182] (3) OER test results:

[0183] The FDCA-MOF loaded glassy carbon electrode (NiFe-FDCA-MOF / / GC) prepared in Example 1 had an OER overpotential as low as 405 mV under alkaline conditions at a current density of 10 mA cm -2 .

[0184] The Fe-FDCA-MOF-supported glassy carbon electrode (Fe-FDCA-MOF / / GC) prepared in Example 2 was tested under alkaline conditions at 10 mA cm⁻¹. -2 At the current density, the OER overpotential is 556mV.

[0185] The Zn-FDCA-MOF-supported glassy carbon electrode (Zn-FDCA-MOF / / GC) prepared in Example 3 was tested under alkaline conditions at 10 mA cm⁻¹. -2 At current densities, the OER overpotential is as low as 534mV.

[0186] The Cu-FDCA-MOF-supported glassy carbon electrode (Cu-FDCA-MOF / / GC) prepared in Example 4 was tested under alkaline conditions at 10 mA cm⁻¹. -2 At current densities, the OER overpotential is as low as 528mV.

[0187] The composition, evaluation results, and OER test results of the MOF materials obtained in the above embodiments are shown in Tables 1, 2, and 3.

[0188] Table 1. Composition, evaluation results, and OER test results of MOF materials.

[0189]

[0190]

[0191] As shown in Table 1, the evaluation results of Examples 1-4 indicate that the two-dimensional mesoporous MOF nanosheet material provided by this invention has large pore size, high yield, and high purity. The method used in Comparative Example 1 has low yield and is time-consuming. Figure 5 As shown, the isotherm of Cu-FDCA in Example 4 is a type IV isotherm, indicating that Cu-FDCA MOF is a mesoporous material. Figure 6 As shown, the isotherm of Cu-BTC in Comparative Example 3 is a type I isotherm, indicating that Cu-BTC MOF is a microporous material. Figure 7 As shown, the NiFe-FDCAMOF-supported glassy carbon electrode in Example 1 operates at 10 mA cm⁻¹. -2 At the current density, the OER overpotential is 405mV.

[0192] Table 2. Spacetime yield, average pore size, and porosity of the examples and comparative examples.

[0193]

[0194] Table 3 Test results in Examples 5-12

[0195]

[0196] From the above Table 1 to Table 3, it can be seen that, compared with the solvothermal method, the electrochemical synthesis method in the embodiment of the present application has a higher space-time yield of the FDCA-based MOF, and compared with the non-FDCA-based (BDC, BTC) MOF, the electrochemical synthesis method has a larger average pore size of the FDCA-based MOF and a lower OER overpotential.

[0197] The embodiments of the present application are described above in combination with the drawings, but the present application is not limited to the specific embodiments described above, and the specific embodiments described above are merely illustrative rather than limiting, and those of ordinary skill in the art can make many forms under the inspiration of the present application without departing from the purpose of the present application and the scope protected by the claims, which all belong to the protection of the present application.

Claims

1. A two-dimensional mesoporous nanomaterial, characterized in that, Comprise: a metal-organic framework material comprising a ligand compound containing a plurality of carboxylate groups connected to metal ions by coordination bonds.

2. The material of claim 1, wherein, the nanomaterial is in a layered or sheet structure; and / or the nanomaterial is in a sheet shape, and the thickness of the nanomaterial is 0.5-20 nm; and / or the nanomaterial has a pore size distribution of 2-50 nm; and / or The nanoparticle has a pore volume of 0.01 to 3.0 cm3 / g. 3 / g.

3. The material of claim 1, wherein, the ligand compound comprises: 2,5-furan dicarboxylic acid.

4. The material of claim 1, wherein the metal ions comprise: at least one of nickel, iron, zinc, copper, manganese, tin, aluminum, bismuth, vanadium, and molybdenum ions.

5. A method for preparing a two-dimensional mesoporous nanomaterial, characterized in that, Comprise: dissolving the ligand compound and the metal source in a solvent to obtain an electrolyte; pouring the electrolyte into an electrolytic cell, and applying a voltage between the anode and the cathode to perform electrochemical synthesis; the time for electrochemical synthesis is 0.1-24 h; separating the nanocompounds generated on the electrodes and the nanocompounds generated in the electrolyte, and drying the nanocompounds to obtain the two-dimensional mesoporous nanomaterial.

6. The preparation method according to claim 5, characterized in that, the reaction temperature for electrochemical synthesis is 0-90℃; and / or the molar ratio of the ligand compound to the metal source is 0.1-10; and / or the voltage is 1-100 V; and / or the anode is selected from at least one of iron sheet, copper sheet, zinc sheet, and nickel sheet, and the cathode is selected from at least one of nickel foam, zinc sheet, copper foam, iron foam, carbon felt, graphite felt, iron sheet, copper sheet, and nickel sheet; and / or before the step of applying a voltage between the anode and the cathode to perform electrochemical synthesis, further comprising: cleaning the anode and the cathode; and / or the step of drying the nanocompounds comprises: placing the nanocompounds in a vacuum dryer at 20-200℃ for 2-12 h.

7. The preparation method according to claim 5, characterized in that, the ligand compound comprises: 2,5-furan dicarboxylic acid; and / or the metal ions comprise: at least one of nickel, iron, zinc, copper, manganese, tin, aluminum, bismuth, vanadium, and molybdenum ions; and / or the metal source is an acetate metal source; and / or the solvent is selected from at least one of dimethylformamide, dimethylacetamide, glacial acetic acid, methanol, ethanol, and water.

8. The preparation method according to claim 5, characterized in that, the electrolyte further comprises: a surfactant.

9. The preparation method according to claim 8, characterized in that, the surfactant comprises: at least one of cetyltrimethylammonium bromide, octadecyltrimethylammonium bromide, dodecyltrimethylammonium bromide, tetrabutylammonium bromide, and tetrabutylammonium tetrafluoroborate; and / or the molar ratio of the metal source to the surfactant is (1:0.01)-(1:5).

10. The nanomaterial of any one of claims 1-4 or the nanomaterial prepared by the preparation method of any one of claims 5-9 for use in electrocatalytic water splitting, electrocatalytic CO2 reduction, photocatalysts, or heterogeneous catalysts.